De novo whole transcriptome analysis of Aeromonas hydrophila isolated from the gut of an infected Labeo rohita - Das, Basanta Kumar; Kumar, Vikash; Das, Priyanka; Nayak, Kausalya K. (Frontiers in Microbiology, 2023)
Aeromonas hydrophila is a major generalist bacterial pathogen causing severe infections and mortalities in aquatic animals. Its genome, which was the first to be sequenced from the Aeromonas genus, may serve as a model for studying pathogenic mechanisms. To explore the pathogen-host fitness mechanism of bacterium, a comprehensive comparative transcriptome ecotype analysis of A. hydrophila isolated from the gut of Labeo rohita during infection was performed. Special characteristics in gene expression, gene ontology terms and expression of pathogenesis-associated genes, including genes encoding secreted proteins, candidate effectors, hydrolases, and proteins involved in secondary metabolite production were revealed. Among the database, 6,533 were gene ontology (GO) annotated, while 1,480 were not allocated in any GO terms. Investigation on GO illustrated that the articulated genes were improved with molecular function, cellular components, and biological processes. Further bioinformatics analysis identified the outer membrane protein genes (ompA, ompts, ompw, omp38, and omp48), cytotoxin, amylase, and lipase genes. Overall, this work allowed to designate, for the first time, a global view on the pathogenicity of Aeromonas hydrophila during infection. Furthermore, the study provides information on the fitness of A. hydrophila, a severe pathogen with a wide host range.